Yemen/China South-South Exchange : Systematic Management of Coastal and Marine Areas - Setlur, Banu; Ari, Ayala Peled Ben (World Bank, Washington, DC, 2012)
In March 2010, a delegation of Yemeni decision makers and practitioners visited five cities in China: Fuzhou, Xiamen City, Xiangshan, Qingdao and Beijing. The Yemeni delegation was headed by Mr. Salem Ahmed Al-Khambashi, Governor of the coastal governorate of Hadramout, and comprised representatives from relevant central and local authorities, the Fisheries Cooperative Union and the private sector. The delegation's aim was to study the country's institutional arrangements for coastal zone management:, to examine integrated coastal zone management (ICZM) arrangements, and the local economics of sustainable fishing. In view of applying the National ICZM Decree (2009), the delegation also sought to better understand the modalities, roles, policies and practices applied towards effective management of coastal zones and the fisheries sector in China. The program was designed based on a needs assessment by Chinese experts who visited Yemen in May 2009 to learn about the country's coastal system.